ROLES OF AGRITOURISM IN UPBRINGING AND EDUCATING CHILDREN AND YOUTH - Płomiński, Arkadiusz; Małolepszy, Eligiusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Agritourism is one of the most popular forms of tourism practised in rural areas. It fulfils a number of functions, including economic, social, health-related and educational one.  Agritourism offer is addressed to all age and social groups. Among children and youth agritourism above all serves an educational and training purpose. In these two processes agritourism farms within the All-Polish Network of Educational Homesteads are particularly important. Educational programmes implemented as part of "Educational Homesteads" are held in the forms of educational and practical classes. The subjects of the classes addressed to children and youth include issues related to regional history and tradition, environment protection, ecology, plant and animal breeding, cuisine, (herbal) medicine, geography, geology and the educational cycle entitled vanishing professions.